PENGEMBANGAN EVALUASI PEMBELAJARAN MENGGUNAKAN APLIKASI QUIZIZZ UNTUK MENINGKATKAN MOTIVASI BELAJAR MATA PELAJARAN IPA SISWA SMP AT-THAHIRIN KABUPATEN BOGOR - Irman; Hendro Prasetyono (STKIP Subang, 2025)
ABSTRACT This study developed learning evaluation using the Quizizz application for eighth-grade science subjects (IPA) at At-Thahiri Junior High School (SMP). The study aimed to determine the level of feasibility and practicality of the developed learning evaluation product. This research used the 3D development model (Define, Design, and Develop). The validation results obtained from the material expert was 79%, categorized as valid. The validation results from the media expert was 91.2%, categorized as very valid. The validation results from the eighth-grade SMP teacher was 96.3%, categorized as very valid. The results from the small-group trial by students was 95.2%, categorized as very practical. The results from the large-group trial by students was 93.5%, categorized as very practical. Based on these results, the learning evaluation product using the Quizizz application is deemed feasible and practical for use in learning. Furthermore, it is expected that this learning evaluation product can be used in elementary school learning for other subjects/materials